Oligodendroglial excitability mediated by glutamatergic inputs and Nav1.2 activation - Emmanuelle Berret (Nature Portfolio, 2017)
Axon-glial communication is important for myelination. Here the authors show that during postnatal development in rats, a subpopulation of pre-myelinating oligodendrocytes in the auditory brainstem receive excitatory inputs and can generate Nav 1.2-driven action potentials, and that such process promotes myelination.